Prototipe Alat Pendeteksi Kelainan Kelenjar Tiroid Dengan Menggabungkan Teknik Iridologi Dan Elektrokardiografi Berbasis Jaringan Saraf Tiruan - Rahmat - -; Defni - -; Firdaus - -; Gustina Indriati - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2015)
Some of the external symptoms of hyperthyroidism may be experienced by people who are not suffering from hyperthyroid disease, therefore needs a thorough examination and diagnosis for patients with hyperthyroidism that drug delivery and targeted therapy. A thorough examination of this costly and quite a long time. This research make a prototype instrumentation to help detect the presence of symptoms of thyroid gland disorders, especially hyperthyroidism, do not use chemicals and does not hurt the patient. The principle of this tool is to combine technology with electrocardiographic Iridology specifically based artificial neural network. In the first year is the design and realization of a prototype of the channel electrocardiograph-based personal computer for measurement of cardiac patients megalami signal abnormalities tachycardia (one of the symptoms of hyperthyroidism). Electrocardiography will measure and display signal to monitor a patient's heart, can store data and make a decision whether the patients had tachycardia heart rhythm disorder or not. In both make iridology devices based neural network to detect any abnormalities of the thyroid gland through the iris image. Electrocardiography device coupled with iridology software in order to get a prototype for the detection of hyperthyroidism through the measurement of two variables: cardiac signal and image of the iris. The Merger is software into a single entity has not done separately but have been able to perform measurements on patients. Tests have been conducted on 8 (eight) patients and has not been accompanied by a doctor, the conclusion of the test is that all patients tested did not experience hyperthyroidism.